EFFECT OF CAPITAL STRUCTURE ON THE PROFITABILITY OF MANUFACTURING COMPANIES - Pipin Desria Marpaung; Jholant Bringg Luck Amelia Br Sinaga; Edward - (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
This research has the objective to see the effect of Capital Structure, Working Capital Turnover, Inventory Turnover, Accounts Receivable Turnover and Asset Growth on Profitability. This population was carried out in all various industrial sector companies, the sample was selected through purposive sampling technique and obtained as many as 12 sample companies. The method used is multiple linear regression. The results showed that working capital turnover, capital structure and inventory turnover had an effect on profitability. Meanwhile, Asset Growth and Accounts Receivable Turnover have no effect on Profitability. And Capital Structure, Accounts Receivable Turnover, Working Capital Turnover, Inventory Turnover and Asset Growth have no stimulant effect on profitability. The amount of determination is 42.2% while the remaining 57.8% of profitability is explained by other variables which are not discussed in this study. So it can be concluded that only the Capital Structure, Inventory Turnover, and Working Capital Turnover have an effect on Profitability in manufacturing companies